Telemedicine in Peru: origin, implementation, pandemic escalation, and prospects in the new normal - Rees, Gareth H. (Oxford University Press, 2024)
For many countries telemedicine was speedily adopted as a result of the COVID-19 pandemic, though for some countries telemedicine may have been implemented in a context of limited regulations or few plans or strategies to scale quickly. This article recounts how telemedicine was developed in Peru as a measure to support the country's Universal Health Coverage and service access to rural and locations with low workforce numbers and its deployment. From a range of data, we find that Peru's development of telehealth began before the pandemic, which by 2020 was sufficient to be able to foster a rapid and wider deployment and while the telemedicine service volumes quickly grew from the pandemic onset, these numbers then begin to reduce suggesting that telemedicine was considered more as a pandemic emergency measure rather than a change to the mix of health provision. From these data we offer two lessons, (i) that Peru's preparedness in terms of telemedicine policy and regulation were helpful to rapidly expand telemedicine at a time of necessity and (ii) that due to this investment and with a better understanding, Peru now has a short-run window of opportunity for the Peruvian Government to continue its regulatory development and investment to further deploy telemedicine services as a UHC improvement measure and to better align the health system to the country’s health needs.
Keywords: Digital Health; Telemedicine; Salud Digital; Peru; Telemedicina; Universal Health Coverage; Perú; Cobertura Universal de Salud; Service development; Desarrollo de servicios; https://purl.org/pe-repo/ocde/ford#5.02.04; https://purl.org/pe-repo/ocde/ford#3.03.02